An experimental investigation on dynamic response of composite panels subjected to hydroelastic impact loading at constant velocities. (15th December 2017) - Hassoon, O.H.; Tarfaoui, M.; El Malki Alaoui, A.
Graphical abstract: Figure: Composite panels under slamming impact: panels and Servo-test machine. Highlights: Dynamic structural response of composite structures under slamming impact. Experimental investigation on the slamming impact water of composite wedge. Damage progressive in composites under slamming impact is presented. Assessment to meet the specific requirements of marine vessels. Abstract: Generally, when marine vessels encounter the water surface on entry and subsequently re-enter the water at high speed, this can subject the bottom section of the vessels to high hydrodynamic loads, especially over very short durations. This phenomenon generates high hydrodynamic loads, which can cause a catastrophic failure in the structure. In contrast, the interaction between deformable structures and free water surface can be modified the fluid flow and changed the estimated hydrodynamic loads comparing with rigid body, due to appearance of hydroelastic effects. These effects are considered active challenge areas in structural ship design. This work presents an experimental study of the water impact for composite laminate wedge at different constant entry velocities. The aim of this study is to investigate the dynamic structural response of panels and predicts the hydrodynamic loads to meet the specific requirements of marine vessels. In order to better describe hydroelastic influence, two composite panels with different thicknesses namely 8 mm and 13 mm are subjected under constant impact velocities of 4, 6 and 8 m/s with the deadrise angle of 10°. The obtained experimental results were indicated that more flexible panels had a higher peak force and significant dynamic noise compared with higher stiffness panels. In addition, the maximum deformation occurred in the centre and close to the chine edge of the panel due to changes in local velocity and local deadrise angle. For this reason, special attention requires in both design phase and operation phase.